2021
DOI: 10.21203/rs.3.rs-223265/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data-driven design of targeted gene panels for estimating immunotherapy biomarkers

Abstract: We introduce a novel data-driven framework for the design of targeted gene panels for estimating exome-wide biomarkers in cancer immunotherapy. Our first goal is to develop a generative model for the profile of mutation across the exome, which allows for gene- and variant type-dependent mutation rates. Based on this model, we then propose a new procedure for estimating biomarkers such as Tumour Mutation Burden and Tumour Indel Burden. Our approach allows the practitioner to select a targeted gene panel of a p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Using the Non-Small Cell Lung Cancer dataset from Campbell et al (2016), we have demonstrated the excellent predictive performance of our proposal for estimating Tumour Mutation Burden and Tumour Indel Burden, and shown that it outperforms the state-of-the-art procedures. Our framework can be applied to any tumour dataset containing annotated mutations, and we provide an R package (Bradley and Cannings, 2021) which implements the methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Non-Small Cell Lung Cancer dataset from Campbell et al (2016), we have demonstrated the excellent predictive performance of our proposal for estimating Tumour Mutation Burden and Tumour Indel Burden, and shown that it outperforms the state-of-the-art procedures. Our framework can be applied to any tumour dataset containing annotated mutations, and we provide an R package (Bradley and Cannings, 2021) which implements the methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results are given in Section 3 and we conclude in Section 4. Finally, we also provide an R package ICBioMark (Bradley and Cannings, 2021) which implements the methodology and reproduces the experimental results in the paper.…”
Section: Introductionmentioning
confidence: 99%